Why God Did Not Choose All Souls: New Scriptural Evidence - Grupp, Jeff ca. 20./21. Jh. (Philosophy & theology, 2020)
An analysis of Scripture uncovers a new model of God's election and predestination of souls, which fits under the umbrella of the Calvinist theologies, but where this model involves an answer to the long-standing question of why God chose some, rather than all. It will be explored how before souls were elected (or condemned), God looked at them and knew them in a pre-election state, which God used to predestine each soul in physical reality. This analysis reveals why it could be no other way but where God only would choose some, rather than all souls during the physical embodiment stage of the soul, and the vexing centuries-old Calvinist question of why God elected some not all has an answer.